The Use of Histology in the Study of Plant Tissue Culture Systems: Some Practical Comments - Yeung, E.C.
Histological methods have contributed significantly to our understanding of in vitro culture systems. A good histological study based on anatomical and histochemicai changes provides insight into cellular processes and provides clues that allow for the proposal of hypotheses for further experimentation. This article serves to draw attention to the use of a histological approach to one's experimental system. Some of the common mistakes in the handling and processing of explants are discussed. A protocol for the plastic embedding method is detailed.
Keywords: HISTOLOGY; PARAFFIN AND PLASTIC EMBEDDING METHODS; PHOTOMICROGRAPHY; STAINING